A model of P2P energy trading for active distribution network based on cooperative game - Li, Yiyang (Nanyang Technological University, 2022)
With the gradual expansion of the scale of distributed generation networks, the operation control of distribution networks is facing the challenges of overload, tremendous loss, and low efficiency. In order to solve these problems, this project introduces the concept of Agent to manage the power consumption and transaction in local areas and establishes a Peer-to-Peer (P2P) energy trading framework where Agents work as transaction individuals representing residential electric power consumers. Here, users can choose whether to trade with a power grid company or other users from the perspective of economic interests. After realizing the optimization of overall economic benefit, the interest conflict between agents is solved by a multiperiod Nash Bargaining theory, which is a cooperative game theory. Finally, based on this framework, the effectiveness of the new model and algorithm is verified by the simulation of the IEEE 37-bus distribution network on MATLAB. The overall relative cost reduction is 13.82%, and users’ demand load curve becomes flattened in the simulation experiment.